A meta-analysis of the association between calprotectin and the severity of COVID-19. Issue 3 (March 2022) - Mao, Qin; Wang, Chunyi; Wen, Wen; Zhou, Mengyun; Tang, Jiake; Chen, Chen; Cheng, Yongran; Wu, Qi; Zhang, Xingwei; Feng, Zhanhui; Wang, Mingwei
Highlights: The severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2)is constantly ravaging the world. Many inflammatory factors(such as C-reactive protein, ferritin, and d -dimer)have been reported as poor prognosis predictors for patients with COVID-19. The role of serum calprotectin levels in severe COVID-19 is controversial. Our results of meta-analysis support calprotectin as an important COVID-19 biomarker, and its clinical use in predicting disease severity.